Dissection of patulin biosynthesis, spatial control and regulation mechanism in Penicillium expansum. (6th March 2019) - Li, Boqiang; Chen, Yong; Zong, Yuanyuan; Shang, Yanjiao; Zhang, Zhanquan; Xu, Xiaodi; Wang, Xiao; Long, Manyuan; Tian, Shiping
Summary: The patulin biosynthesis is one of model pathways in an understanding of secondary metabolite biology and network novelties in fungi. However, molecular regulation mechanism of patulin biosynthesis and contribution of each gene related to the different catalytic enzymes in the biochemical steps of the pathway remain largely unknown in fungi. In this study, the genetic components of patulin biosynthetic pathway were systematically dissected in Penicillium expansum, which is an important fungal pathogen and patulin producer in harvested fruits and vegetables. Our results revealed that all the 15 genes in the cluster are involved in patulin biosynthesis. Proteins encoded by those genes are compartmentalized in various subcellular locations, including cytosol, nucleus, vacuole, endoplasmic reticulum, plasma membrane and cell wall. The subcellular localizations of some proteins, such as PatE and PatH, are required for the patulin production. Further, the functions of eight enzymes in the 10‐step patulin biosynthetic pathway were verified in P. expansum . Moreover, velvet family proteins, VeA, VelB and VelC, were proved to be involved in the regulation of patulin biosynthesis, but not VosA. These findings provide a thorough understanding of the biosynthesis pathway, spatial control and regulation mechanism of patulin in fungi.